Organosulfonic acid-functionalized biomass-derived carbon as a catalyst for glycerol acetylation and optimization studies via response surface methodology - Nda-Umar, Usman Idris; Ramli, Irmawati; Muhamad, Ernee Noryana; Azri, Norsahida; Ishak, Nor Shafizah; Yahaya, Muhamad; Yap, Yun Hin @ Md. Taufiq (Elsevier B.V, 2021)
Organosulfonic acid-functionalized biomass-derived carbon catalysts were developed using different aryl and alkyl sulfonating reagents at low concentrations. The catalysts were characterized using advanced analytical techniques and evaluated in glycerol acetylation in a batch reflux reactor. Results indicated that the catalyst obtained from the functionalization of palm kernel shell with ethanesulfonic acid (ESA) exhibited better performance in terms of glycerol conversion and triacetin selectivity. Response surface methodology (RSM) was used to develop empirical models to optimize the reaction conditions and subsequently validated. Average values of 99.03§0.14% GC, 6.91§0.56, 54.86§0.42, and 37.73§0.21% selectivity to monoacetin, diacetin and triacetin, respectively were achieved at the optimum conditions of temperature 120§2 °C, glycerol to acetic acid mole ratio of 1:8, catalyst load of 0.69 g and reaction time of 3 h. The models were statistically analyzed and exhibited a good fit with agreement between the predicted and the experimental data, the determination coefficient (R2 ) > 0.9500 and adequate signal-to-noise ratio >4. The effects of the reaction variables and their interaction were further explained using the models and the surface response plots. On the reusability test, the catalyst exhibited excellent performance in glycerol conversion and diacetin selectivity for the five reaction cycles but was inferior in the selectivity to triacetin, stabilizes only after the first reaction cycle at a reduced level, due to leaching of the acidic sites.